2020
DOI: 10.1038/s41539-020-0063-z
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relationship of favorable weight change to academic performance in children

Abstract: Although there is a growing consensus about the positive relationship between prevention of overweight/obesity and academic performance in children, relevant studies targeting the relationship between underweight and academic performance are scarce. This study aimed to examine the longitudinal relationship of favorable weight change to academic performance in schoolchildren. We analyzed 2-year longitudinal data derived from 197 seventh-grade children aged 12-13 years. Academic performance was assessed using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…A recent study on the physical health of Chinese college students reported that the overweight and obesity rates were increasing yearly among the college students [ 3 ]. Remarkably, overweight/obesity in early adulthood are associated with higher risks of cardiovascular disease in late life [ 4 , 5 ], and it also negatively affects academic performance [ 6 , 7 , 8 ] and executive control (EC), becoming evident in accelerated cognitive decline and brain atrophy in later years [ 9 , 10 ]. Executive control plays a pivotal role in executive functions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on the physical health of Chinese college students reported that the overweight and obesity rates were increasing yearly among the college students [ 3 ]. Remarkably, overweight/obesity in early adulthood are associated with higher risks of cardiovascular disease in late life [ 4 , 5 ], and it also negatively affects academic performance [ 6 , 7 , 8 ] and executive control (EC), becoming evident in accelerated cognitive decline and brain atrophy in later years [ 9 , 10 ]. Executive control plays a pivotal role in executive functions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Findings from multinational studies have shown that children whose stunting status improved at 5, 6, and 8 y of age performed better in cognitive tests than those who remained stunted throughout or performed similarly to those who were never stunted ( 13 , 30 , 39 ). Similarly, weight gain in underweight Japanese children aged 12–13 y had a positive effect on their academic performance, independently of socioeconomic and lifestyle factors ( 48 ). A randomized controlled trial in Indian adolescent girls and boys found that consumption of high iron-biofortified pearl millet during school meals for 6 mo corrected iron deficiency and improved performance on computerized tests of attention and memory ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, after controlling for BMI z-scores, waist circumference, and body fat percentage, the levels of aerobic fitness and motor skills were positively correlated with the grades on math and language tests among 6-18-year-old adolescents (Esteban-Cornejo et al, 2014). Similarly, in Japan, cardiorespiratory fitness and overall health-related fitness were found to have significant positive effect on academic performance among middle school students (Ishihara et al, 2018). Meanwhile, in a study involving 183 college students examining the relationship between physical fitness and academic performance, it was found that, apart from body mass index (BMI), all students' physical fitness tests showed a significant positive correlation with average academic scores, indicating that high levels of physical fitness contribute positively to academic success (Başkurt et al, 2020).…”
Section: Introductionmentioning
confidence: 87%